2013
DOI: 10.1038/srep01251
|View full text |Cite
|
Sign up to set email alerts
|

Common dynamical features of sensory adaptation in photoreceptors and olfactory sensory neurons

Abstract: Sensory systems adapt, i.e., they adjust their sensitivity to external stimuli according to the ambient level. In this paper we show that single cell electrophysiological responses of vertebrate olfactory receptors and of photoreceptors to different input protocols exhibit several common features related to adaptation, and that these features can be used to investigate the dynamical structure of the feedback regulation responsible for the adaptation. In particular, we point out that two different forms of adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…24, 25 Similarly, in the cardiovascular system, it has been previously shown that sympathetic nerve activity measured by muscle sympathetic nerve activity was greater when the heart was paced irregularly, and these findings were independent of hemodynamic changes. 26 We speculate that variability of PVC CI compared to fixed CI may prevent neural adaptation and play an important role in reflex activation of the ANS.…”
Section: Discussionmentioning
confidence: 90%
“…24, 25 Similarly, in the cardiovascular system, it has been previously shown that sympathetic nerve activity measured by muscle sympathetic nerve activity was greater when the heart was paced irregularly, and these findings were independent of hemodynamic changes. 26 We speculate that variability of PVC CI compared to fixed CI may prevent neural adaptation and play an important role in reflex activation of the ANS.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly to Drosophila Or-expressing OSNs, sensory neurons in many other modalities, such as hair cells (49) adaptation in other senses. With respect to modeling, it remains a challenge to understand the general effects of adaptation according to the underlying molecular mechanisms in sensory neurons (50), as has been done in the simpler case of bacterial chemotaxis (51). The ability of strong adaptation by Ors would allow Drosophila to track odor changes over a broad range of concentrations and to detect other odors even in the presence of certain background odor.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociated rods were obtained from adult male Xenopus laevis frogs (Xenopus express, Ancienne Ecole de Vernassal, Le Bourg, France) as previously reported (62,63). OS lengths for green-sensitive and blue-sensitive rods (64) where 31 ± 1 ÎŒm (n = 85) and 26 ± 1.5 ÎŒm (n = 17), respectively, and the OS diameter is about 4-6 ÎŒm.…”
Section: Methodsmentioning
confidence: 99%